2022
DOI: 10.3390/molecules27123773
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of the X + C2H6 [X ≡ H, F(2P), Cl(2P), O(3P), OH] Hydrogen Abstraction Reactions: A Theoretical Review

Abstract: This paper is a detailed review of the chemistry of medium-size reactive systems using the following hydrogen abstraction reactions with ethane, X + C2H6 ® HX + C2H5; X ≡ H, F(2P), Cl(2P), O(3P) and OH, and focusing attention mainly on the theoretical developments. These bimolecular reactions range from exothermic to endothermic systems and from barrierless to high classical barriers of activation. Thus, the topography of the reactive systems changes from reaction to reaction with the presence or not of stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…22,23 In particular, most of these reactions possess van der Waals wells in the reactant and product valleys, and the depth of the wells varies with the reactions. [24][25][26][27] Considering that the depth the of van der Waals well may have a critical impact on the reaction rate constant, three different reactions (i.e. H + C 2 H 6 , Cl + C 2 H 6 and OH + C 2 H 6 ) are chosen in the present paper, which differ in the depth of the van der Waals well.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In particular, most of these reactions possess van der Waals wells in the reactant and product valleys, and the depth of the wells varies with the reactions. [24][25][26][27] Considering that the depth the of van der Waals well may have a critical impact on the reaction rate constant, three different reactions (i.e. H + C 2 H 6 , Cl + C 2 H 6 and OH + C 2 H 6 ) are chosen in the present paper, which differ in the depth of the van der Waals well.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of polyatomic systems this goal is far from being achieved. Recently, our group has analysed this problem 1 by studying the current status of the X + C2H6 [X H, F( 2 P), Cl( 2 P), O( 3 P), OH] hydrogen abstraction reactions. We concluded that the experiment/theory comparison worsens when we go from macroscopic properties (average properties, such as the rate constants) to microscopic properties (state-to-state properties, such as product vibrational distribution).…”
Section: Introductionmentioning
confidence: 99%